Conditioning for strength and human performance - Chandler, T. Jeff; Brown, Lee E. (Routledge, 2019)
Fully revised and updated, the third edition of Conditioning for Strength and Human Performance provides strength and conditioning students with the clearest and most accessible introduction to the scientific principles underpinning the discipline. Covering bioenergetics and nutrition, a systematic approach to physiological and endocrinological adaptations to training and the biomechanics of resistance training, no other book provides such a thorough grounding in the science of strength and conditioning or better prepares students for evidence-based practice.